Barriers and facilitators to cervical cancer screening among Pakistani and Somali immigrant women in Oslo: a qualitative study - Gele AA; Qureshi SA; Kour P; Kumar B; Diaz E (Dove Medical Press, 2017)
Abdi A Gele,1,2 Samera A Qureshi,1 Prabhjot Kour,1 Bernadette Kumar,1 Esperanza Diaz1,3 1Norwegian Center for Minority Health Research, 2Department of Health, Institute of Nursing and Health Promotion, Oslo and Akershus University College, Oslo; 3Department of Global Public Health and Primary Care, University of Bergen, Bergen, Norway Abstract: Norway has a low incidence and mortality rate of cervical cancer, which is mainly due to the high participation rate of women in cervical cancer screening. However, the attendance of cervical cancer screening was reported to be low among immigrant women. For this reason, we conducted a qualitative study to obtain better insight into perceived barriers and challenges to cervical cancer screening among Somali and Pakistani women in the Oslo region. A convenient sample of 35 (18 Pakistani, 17 Somali) women were recruited for the study in collaboration with Somali and Pakistani community partners. Focus group discussions were used to explore barriers and facilitators to cervical cancer screening, whereas the Ecological Model was used as the framework for the study. The study found three levels of barriers to cervical cancer screening. The individual level included a lack of understanding of the benefits of the screening. The sociocultural level included the stigma attached to the disease and the belief that women who are unmarried are sexually inactive. The system-related level included a lack of trust toward the health care system. Based on the study results, and using a common denominator approach for the immigrant groups included, the study recommends three communication strategies with the potential to improve women’s participation in cervical cancer screening: 1) in-person communication and information material at health centers; 2) verbal communication with women through seminars and workshops to educate them about their risk of cancer and the importance of screening and 3) the initiation of better recall through SMS and letters written in native languages. Finally, an intervention study that compares the aforementioned strategies and proves their effectiveness in increasing immigrant women’s participation in cervical cancer screening is recommended. Keywords: cervical cancer, immigrant women, Somali and Pakistani women, preventive health